(Més)aventures d’une coalition contestataire : le cas de la Coordination nationale pour le changement et la démocratie (CNCD) en Algérie - Layla Baamara (L’Année du Maghreb)
Created on January 21, 2011 in the aftermath of riots across the country, the National Coordination for Change and Democracy (NCCD) called for forces to rally and denounce the repression. Whether collectively or individually, formally organized or not, a number of players gathered around the initiative. From January to June 2011, hundreds of people repeatedly convened in Algiers and called for the “fall of the regime”, thereby defying the ban on demonstrations in the capital. These movements met with minor success at mobilization, which contrasted with the magnitude and recurrence of sectorial protests. Beyond the measures implemented by the government and despite low popular interest, interviews and on-site observations led to uncertainties about the logic and dynamics at work in this unique coalition. We explored the scope and practical aspects of the convergence of players whose differences have marked recent decades, and the tensions in the coordination, to better understand the power relations that pervade the protest space. An analysis of the processes that have shaped the formation, evolution and disintegration of the coalition may then shed light on the logic of collective protest action in Algeria.